2014
DOI: 10.1128/aem.00554-14
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Symbionts of a Devastating Coffee Plant Pest, the Stinkbug Antestiopsis thunbergii (Hemiptera: Pentatomidae)

Abstract: dStinkbugs of the genus Antestiopsis, so-called antestia bugs or variegated coffee bugs, are notorious pests of coffee plants in Africa. We investigated the symbiotic bacteria associated with Antestiopsis thunbergii, a major coffee plant pest in Rwanda. PCR, cloning, sequencing, and phylogenetic analysis of bacterial genes identified four distinct bacterial lineages associated with A. thunbergii: a gammaproteobacterial gut symbiont and symbionts representing the genera Sodalis, Spiroplasma, and Rickettsia. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…In addition to the 16S rRNA gene sequences of the gut symbiotic bacteria of the pentatomid stinkbugs determined in this study, we retrieved already-published 16S rRNA gene sequences of gut symbiotic bacteria of pentatomid stinkbugs [1315, 2022, 26, 28] (Additional file 2), those of gut symbiotic bacteria of other stinkbugs representing the families Scutelleridae, Cydnidae, Parastrachiidae, Acanthosomatidae, Plataspidae and Urostylididae [15, 18, 25, 3741] (Additional file 2), and those of closely-related free-living bacteria [4252] (Additional file 2). Molecular phylogenetic analysis revealed that the gut symbionts of the pentatomid stinkbugs were all placed within the Enterobacteriaceae of the γ-Proteobacteria (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the 16S rRNA gene sequences of the gut symbiotic bacteria of the pentatomid stinkbugs determined in this study, we retrieved already-published 16S rRNA gene sequences of gut symbiotic bacteria of pentatomid stinkbugs [1315, 2022, 26, 28] (Additional file 2), those of gut symbiotic bacteria of other stinkbugs representing the families Scutelleridae, Cydnidae, Parastrachiidae, Acanthosomatidae, Plataspidae and Urostylididae [15, 18, 25, 3741] (Additional file 2), and those of closely-related free-living bacteria [4252] (Additional file 2). Molecular phylogenetic analysis revealed that the gut symbionts of the pentatomid stinkbugs were all placed within the Enterobacteriaceae of the γ-Proteobacteria (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the families Pentatomidae and Cydnidae, by contrast, the symbiont phylogeny is not concordant with the host phylogeny, and the symbiont genomes exhibit no or moderate size reduction, suggesting relatively younger host–symbiont associations through acquisitions, horizontal transfers, and/or replacements of the symbiotic bacteria [13, 17, 20, 22, 23, 25]. Recent studies have revealed the striking diversity and dynamic evolutionary trajectories of gut symbiotic bacteria in the stinkbug family Pentatomidae: all gut symbiotic bacteria belong to the Enterobacteriaceae of the γ-Proteobacteria [10, 1315, 20–24, 2628]; however, the symbiotic bacteria are polyphyletic and their phylogeny does not reflect the phylogeny of their host stinkbugs, suggesting multiple evolutionary origins of the symbiotic bacteria from Pantoea spp. and allied γ-proteobacteria [13, 20, 22, 23, 27, 28]; some symbionts are uncultivable whereas others can be cultivated outside the host body [22].…”
Section: Introductionmentioning
confidence: 99%
“…4). Such obligate symbiotic bacteria associated with the midgut symbiotic organs have been described from a variety of stinkbugs of the families Pentatomidae (15,17,18,20,21,34,44), Scutelleridae (16,45,46), Cydnidae (19), Plataspidae (24,25,47,48), Acanthosomatidae (14), Parastrachiidae (22), Urostylididae (26), and others. As are the cases of the gut symbiotic bacteria associated with the stinkbugs representing the superfamily Pentatomoidea (21,49,50), the gut symbiont of P. splendens was placed within the Enterobacteriaceae of the Gammaproteobacteria, in contrast to the betaproteobacterial gut symbionts widely found across the superfamilies Lygaeoidea and Coreoidea (5).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that a variety of biological roles other than nutritional ones are attributed to facultative bacterial symbionts of diverse insects (55) and that many stinkbugs harbor not only the obligate gut symbionts but also facultative bacterial symbionts like Wolbachia, Sodalis, Rickettsia, Spiroplasma, Lariskella, etc. (44,(56)(57)(58), the possibility of nonnutritional roles of the symbiont should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Far less is known about Sodalis in bees and, though it has been previously identified in association with the bee genera Ceratina and Osmia, (36,61), it has not previously been examined in detail. The diversity of insects that play host to Sodalis is quite wide, spanning lice, beetles, flies, many hemipterans, and, now, bees (31,51,(62)(63)(64)(65)(66)(67). Where best-studied, in the rice weevil Sitophilus oryzae and the tsetse fly Glossina morsitans, the functional consequences of Sodalis symbiosis appear to vary.…”
Section: Discussionmentioning
confidence: 99%